Accounting comparability and cash flows versus accruals. Issue 5 (11th October 2021) - Cheng, Mengyao
Abstract : Purpose: This study aims to examine whether accounting comparability between two firms, as measured by De Franco et al. (2011), reflects closeness in the amounts of cash flows and accruals between the firms. Design/methodology/approach: Using 278, 452 pair-year observations over the years 2003–2019, the author evaluates the research question using regression models. Findings: Closeness in cash flows and closeness in accruals both increase accounting comparability and the effect of closeness in cash flows is greater. The effect of closeness in earnings is greater than the combined effects of closeness in cash flows and accruals. Earnings quality strengthens, while product closeness weakens, the effects of closeness in earnings and closeness in cash flows. Originality/value: To the best of the authors' knowledge, this study is the first to empirically test the link between the closeness in earnings components and accounting comparability. This study is also the first to examine cash flows versus accruals in the context of accounting comparability.